Spatio-Temporal Simulation of Hydrological Elements and Disaster Causes in Beijiang River Basin - ZHANG Kangtao; LEI Weidong (Renmin Zhujiang)
Soil saturation, coupled with intense rainfall can lead to severe flooding and geological disasters, and understanding the spatiotemporal distribution of hydrological elements within a given region is critical for effective disaster mitigation. The CREST distributed hydrological model, incorporating distributed parameters such as soil water capacity and saturated hydraulic conductivity, was used to simulate runoff processes in Beijiang River Basin from 2019 to 2022. The analysis focused on the spatiotemporal distribution characteristics of precipitation, soil moisture, and runoff before and after the once-in-a-century flood that occurred on June 21, 2022, and further explored the relationship among hydrological elements, landslides, and floods. The results show that the Nash-Sutcliffe efficiency coefficients (NSEs) of the model are 0.84 and 0.82, and Pearson correlation coefficients (CCs) are 0.92 and 0.91, respectively, in the periodic and validation periods. The relative deviation is small, indicating that the CREST model has high simulation accuracy in the Beijiang River Basin. The results find that prior to the once-in-a-century flood event on June 21, 2022, the soil moisture levels across the basin were generally high. As the precipitation continued, the soil approached full saturation, and downstream discharge exceeded 16 000 m3/s. After the flood, as precipitation decreased, both soil moisture and runoff levels dropped. A comparison between the simulated average soil moisture for 2022 and historical landslide locations reveals that areas with high kernel density of historical landslides overlap with regions with high soil moisture in the southeastern part of the basin. Comprehensively, the southeastern region, located downstream, faces a higher risk of combined flood and geological hazards during the flood season.